Condyle dislocation following mandibular reconstruction using a fibula free flap: complication cases - Sang-Hoon Kang; Sanghoon Lee; Woong Nam (SpringerOpen, 2019)
Abstract Background Condylar dislocation can arise as a complication in patients who required mandibular and/or condylar reconstruction and were operated on with fibula free flap (FFF) using surgical guides designed using simulation surgery. Surgeons should be aware of the complications in these present cases when planning and performing reconstructions as well as predicting prognoses. Cases presentation Two cases showed condylar dislocation in mandibular reconstruction using a FFF fixed with a reconstruction plate. Three cases showed condylar dislocation in mandibular reconstruction using a fibula free flap fixed with a mini-plate. Conclusion Despite the lack of clinical symptoms in these cases following mandibular reconstruction using an FFF, the mandibular condyle was severely displaced away from the glenoid fossa. A surgeon must have sufficient time to consider the use of a long flap with thickness similar to that of the mandible, ways to minimize span and bending, and methods of fixation. The patient, moreover, should be educated on condylar dislocation. Customized CAD/CAM-prototyped temporomandibular condyle-connected plates may be a good alternative even if virtual simulation surgery is to be performed before surgery. These considerations may help reduce the incidence of complications after mandibular reconstruction.